Effect of the shot peening process on the fatigue strength of SAE 5160 steel - Jaramillo S, Héctor E; de Sánchez, Nelly Alba; Avila D, Julian A [UNESP] (SAGE Publications, 2019)
The fatigue behaviour of SAE 5160 steel was evaluated before and after applying a shot peening process by using different Almen intensities and surface coverings (uncovered, partial coverage and total coverage). In the high-cycle fatigue tests, maximum stresses of 0.8Sut, 0.7Sut and 0.6Sut were applied in the three-point bending test on an Instron 8872 servo-hydraulic machine at a frequency of 10 Hz and a constant stress ratio of Smin/Smax = 0.2 for all tests. The fatigue tests were performed based on the ASTM E8, the specimens were classified into six groups for each stress evaluated, and each group consisted of three standardised specimens (ASTM E466). Also, yield strength, ultimate strength, hardness and microhardness were obtained. The Wilcoxon’s non-parametric test was used to statistically compare all the mechanical properties obtained from the base material with those obtained after the application of the shot peening, for the different surface coverings and Almen intensities. The results showed that the shot peening process significantly increases the fatigue strength of the material, with a 94% increase in fatigue strength of the fully coated specimens. However, no significant increase in fatigue strength was found due to a change in the Almen intensity value. A high correlation factor was found between the increase in the ultimate resistance and the increase in Almen intensity; however, for the yield stress the correlation was medium and inverse. For hardness and microhardness, the correlation factor was very low. Finally, the microhardness values revealed a 3% increase in Vickers microhardness of the shot peening specimens compared to the untreated specimens.
Keywords: fatigue strength; SAE 5160 steel; shot peening; Vickers microhardness